HMSIW based highly selective filter for radar applications. Issue 2 (4th July 2020) - Mahant, Keyur; Mewada, Hiren K.; Patel, Amit V.; Vala, Alpesh; Chaudhari, Jitendra
Abstract : Purpose: This paper aims to present, design and implement a novel half-mode substrate integrated waveguide (HMSIW)-based narrow bandpass filter, which offers advantages like low insertion loss, compact size and high selectivity. Proposed filter will be used in the K-band automotive radar application. Design/methodology/approach: The filtering response in the proposed design is achieved by inserting inductive posts in the HMSIW cavity. Ansoft high frequency structure Simulator (HFSS) is used for the simulation of the proposed structure, which is a three-dimensional full-wave solver using the finite element method (FEM). The proposed filter is fabricated on the dielectric material RT duroid 5, 880 with the dielectric constant ɛ r = 2.2, dissipation factor t and = 4 × 10 –4 and height h = 0.508 mm. Findings: Frequency tuning is also carried out by changing the lateral distance between two inductive posts. Moreover, a comparison of the proposed structure with the previously published work is presented. Proposed method provides the unique advantages such as low insertion loss, high selectivity and compact in size. Originality/value: Indigenous method has been used for the development of the filter. Proposed filter will be used in transmitter subsystem of the K-band radar system operating at the center frequency of 11.2 GHz. Measurement results are well-matched with the simulated one. Obtained measured result shows return loss of 20.39 dB and insertion loss of 1.59 dB with 3 dB fractional bandwidth (FBW) of 2.58% at the center frequency of 11.2 GHz.